The impacts of covid-19 on municipal and clinical solid waste generation in Selangor throughout 2019-2021 - Ahmad Tajuddin, Husna; Mansor, Mariatul Fadzillah; Nordin, Noor Faizul Hadry (Faculty of Engineering, International Islamic University Malaysia., 2023)
Selangor, like many other Malaysian states, experienced various disruptions due to the COVID-19 pandemic. In addition to health and economic challenges, the populous state also faced notable issues regarding waste production. The pandemic has led to a dramatic rise in solid waste generation especially in its two largest sources, municipal solid waste (MSW) and clinical solid waste (CSW). Though, it is unclear which waste source is more affected by the pandemic. In the present study, the trend of solid waste generation in Selangor during the pandemic was investigated. A comparative statistical analysis was also made between the annual generation rates of both MSW and CSW, particularly spanning the period from 2019 to 2021. After collecting relevant numeric data from respective resources, the data is recorded into Microsoft Excel to generate graphs. The analysis uncovered that MSW exhibited an average annual generation rate of 4.52%, whereas CSW demonstrated a higher average generation rate of 33.03%. An upward trend was seen in both MSW and CSW generation in Selangor from 2019 to 2021, with CSW demonstrating a significantly higher generation rate. The increased generation of CSW during the COVID-19 pandemic emphasizes the need for adhering to appropriate waste management practices. Failure to do so can result in serious consequences, including environmental harm.